Production and Regeneration Protoplast of Dark-Septate Endophytic Fungus Veronaeopsis simplex - Khastini, Rida Oktorida (Proceeding International Conference on Global Resource Conservation, 2013)
The hyphomycete, Veronaeopsis simplex, belongs to the group of so-called dark septate endophytes (DSE) colonize root plant intra and intercellulary without causing harm for the plant host. Knowledge about fungus interaction with the host plant is little. This paper describes the influence of different cultural conditions on protoplast isolation and regeneration from V. simplex fungus. As protoplast is interesting structure that can be used on developing an engineered DSE fungus by mutagenesis or genetic transformation, this research will provide the foundation for further study in order to reveal the unknown mechanism of the fungal role in the plant host. The mycelia age, osmotic stabilizer and lytic enzyme were the main factor that affected the protoplast formation.Â  The maximum yield of protoplast was 3.2 x 106/g fresh mycelia was obtained from 1 week old mycelia digested with the mixed of 1.5% cellulose, 1 % macerozyme and 1.5 % lysozyme for 3 h incubation at 37oC in the dark. Morphology and structure of protoplast released were observed using microscope. It was found that the regeneration of protoplast was possible after being cultivated on both CMMY and PDA medium supplemented with 0.6 M sucrose.Keywords: DSE, isolation, regeneration, protoplast, Veronaeopsis simplexÂ